Cost estimation for rearing dairy young stock in Sabah, Malaysia: a stochastic model accounting for calf mortality uncertainty - Ang, Xin Tong; Sithambaram, Shanmugavelu; Hiew, Mark Wen Han; Khairuddin, Uswah; Shapiai, Mohd Ibrahim; Mohd Suhaimi, Nurul Aisyah; Mohd Nor, Norhariani (Institute of Agricultural Economics Nonprofit Kft., 2024)
The rearing of young stock in tropical countries is considered a substantial investment for dairy farmers due to non-productivity and the higher risk of mortality in the first 2 to 3 years of youngstock life. ICalculating the rearing costs of young calves, espe-cially on non-commercial farms, is challenging due to incomplete farm records. This study, which was conducted at Keningau, Sabah, East Malaysia, estimated the costs of rearing dairy young stock from birth to the first calving age, taking into account uncertainty regarding young stock mortality. A stochastic bioeconomic model was developed at the animal level to calculate the cost of young stock rearing. Our results revealed that the average total costs of rearing dairy young stock from birth to the first calving age for non-commercial and commercial farms were €1,689 and €1,645, with average mortality costs of €15 (0.88%) and €13 (0.79%), respectively. The first calving age of dairy young stock were 32.1 months (442.87 kg) and 24 months (585 kg) in non-commercial and commercial farms, respectively. Sensitivity analysis showed that a 2% decrease in mortality rate reduced rearing costs by €7 for non-commercial farms and €5 for commercial farms. In conclusion, non-commercial (small-scale) dairy farmers should pay more attention to the control and prevention of diseases to reduce mortality, as higher mortality rates have greater cost implications for smaller herds without proper health management.